How I learned to fly - Stine, R. L. (New York : Scholastic Inc., 1997)
Jack has learned how to fly, but things on earth are getting scary.
"An Apple paperback."
RL: 4.
IL: 008-012.
370
Accelerated Reader AR
Keywords: Human locomotion -- Fiction; Horror tales; Flight -- Fiction; Horror stories